Pembuktian Ilmiah Norma Kawasan Hutan Dalam Undang – Undang Nomor 18 Tahun 2013 Tentang Pencegahan dan Pemberantasan Perusakan Hutan (Perkara 333/Pid.B/2014/ Pn.Ptk Jo. 99/Pid Sus/2014/ PT. Ptk JO. Nomor : 1091 K/Pid.Sus/2015) - Jimmi Dohar Pandapotan; Handar Subhandi Bakhtiar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
That the Earth of Indonesia has very extensive forests and dense trees, the International World calls Indonesia the lungs of the world because it can release oxygen from so many trees. Whereas furthermore, with this large number of trees as State forests, protection must be made with the Forestry Law and the Prevention and Eradication of Forest Damage so that the community in general can be protected both from environmental pollution and natural erosion, floods and/or landslides.The fact is that up to now there are still many perpetrators of forest destruction crimes which result in losses to the state, society and the surrounding environment. Normative legal research or library legal research, with a statutory approach, a conceptual approach, a comparative approach, a historical approach. The nature of the research used in this research is descriptive-prescriptive, the author uses content analysis. That protection for the community against forest damage in general already exists in Law Number 32 of 2009 concerning Environmental Protection and Management Jo. Law 31 of 1999 concerning forestry Jo. Law number 18 of 2013 concerning the prevention and eradication of forests, but implementation regarding law enforcement by Forestry Law Enforcers is less than optimal and there are also legal loopholes in the law, so there is a need for cooperation between the community and the government.